Cognitive Behavioral Group Therapy Reduces Stress and Improves the Quality of Life in Patients with Parkinson’s Disease - Hadinia, Anousha; Meyer, Antonia; Bruegger, Viviane; Hatz, Florian; Nowak, Karolina; Taub, Ethan; Nyberg, Elisabeth; Stieglitz, Rolf-Dieter; Fuhr, Peter; Gschwandtner, Ute (Frontiers in Psychology, 2017)
Abstract Objective: The aim of this study is to compare a Cognitive Behavioral Group Therapy (CBT) with a health enhancement program (HEP) for stress reduction and the impact on quality of life (QoL) in patients with Parkinson`s disease (PD). Method: Thirty patients with PD participated in the study: 16 received CBT including stress-reducing elements and 14 took part in a HEP. The two groups did not differ significantly in their baseline demographic characteristics. The patients in both groups underwent weekly sessions of 2 hours’ duration for 9 weeks. The Parkinson`s Disease Questionnaire with 39 items (PDQ-39), the Burden Questionnaire for Parkinson`s Disease (translated from the original German: Belastungsfragebogen für Parkinsonpatienten (BELA)) and the Disease-Related Questionnaire (Fragebogen zur krankheitsbezogenen Kommunikation (FKK)) were primary outcomes. Ratings were completed at baseline and after 9 weeks (immediately after the last treatment session). Results: The patients in the CBT group achieved significantly better BELA, FKK and PDQ-39 scores (p<0.05). Subscale analysis revealed that the scores on the BELA subscales “emotional well-being” and “somatic motor function” contributed significantly to stress reduction (p<0.05). The FKK revealed significant improvement in social skills in the CBT group (p<0.05). Conclusion: Cognitive Behavioral Group Therapy appears to be an effective way for patients with PD to lessen stress and improve their quality of life.